2006
DOI: 10.1002/cite.200600018
|View full text |Cite
|
Sign up to set email alerts
|

Einfluss der Morphologie auf Stofftransport und ‐umsatz in Aspergillus niger‐Pellets

Abstract: Sowohl der Stofftransport als auch der Stoffumsatz in Pilzpellets von

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Additionally, cultivation in loose mycelia form can often result in fouling of reactor internals, such as the sensors. Mass transport in the pellets can be one of the disadvantages of pellet morphology which might also affect the productivity [30].…”
Section: Morphology Of Penicillium Sp During Fermentationsmentioning
confidence: 99%
“…Additionally, cultivation in loose mycelia form can often result in fouling of reactor internals, such as the sensors. Mass transport in the pellets can be one of the disadvantages of pellet morphology which might also affect the productivity [30].…”
Section: Morphology Of Penicillium Sp During Fermentationsmentioning
confidence: 99%
“…A higher surface-to-volume ratio in smaller pellets and different peripheral hyphae structures are assumed to support nutrient uptake [ 56 ]. For hairy and compact pellet structures, even if pellet size remained identical, completely different oxygen consumption rates were shown [ 54 ]. Thus, the different pellet morphology of the wild type might be the reason for the observed limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Besides changes in the nutrient uptake and oxygen supply [ 54 , 58 60 ], pellet formation leads to different grades of heterogeneity of the cells accumulated in the pellets [ 61 63 ]. The use of isoenzymes was seen for several pathways in the wild type strain, which might be explained by higher cell heterogeneity within the pellets.…”
Section: Discussionmentioning
confidence: 99%
“…However, in practice, pellets have an almost spherical geometry and a spherically symmetrical density distribution. Morphological investigations on equatorial sections have also shown that the filament distribution and the mass density within a pellet can vary considerably radially [25,92,135]. In addition, recent microscopic measurements confirm that the pellet density can vary significantly depending on the radius, see Figure 5.…”
Section: Fluidmechanical Models To Describe the Pellet Morphology Andmentioning
confidence: 96%